Correlation between Carcinoma Percentage (CP) and Lymphatic Microvessel Density (LMVD) Based on D2-30/Podoplanin as Metastatic Prognostic Factor to Lymph Nodes in not Otherwise Specified (NOS) Colorectal Adenocarcinoma - Elisabeth Indria Sari; Ening Krisnuhoni; Puspita Eka Wuyung (The Indonesian Society for Digestive Endoscopy, 2017)
Background: In colorectal carcinoma (CRC), myofibroblast are the main component cells in tumour stroma which have an important role in the metastases process. The precentage between carcinoma and desmoplastic stroma known as carcinoma percentage (CP), can be used as an independent predictor metastases. D2-40/Podoplanin (PDPN) known as a spesific marker for lymphatic endothelial cell (LEC), which used to assess lymphatic microvessel density (LMVD) and lymphatic vessel invasion (LVI). This study aims to determine correlation and association between CP, LMVD and LVI with the metastases process to lymph node (LN).Method: CP assessment conducted on 44 samples of adenocarcinoma not otherwise specified (NOS) colorectal were divided into 22 cases with CP-High and 22 cases with CP-Low and examination D2-40/Podoplanin to assess LMVD and LVI. The statistical test is performed to find the correlation between CP and LMVD, as well as the relationship between CP, LVI and metastasis KGB.Results: There were a strong correlation between CP and LMVD intratumoral and peritumoral area with the negative correlation. There were a significant association (p=0,00) between LMVD (intratumoral and peritumoral area) with the LVI. There was a significant association between LVI and lymph node metastases (p = 0,03). Intratumoral area showed significant association with lymph node metastases (p = 0,04), whereas peritumoral area showed no significant association (p = 0,17).Conclusion: CP examination in histopathology specimen can be used to predict high/low rate of tumour cells metastases to the lymph node, based on a strong correlation between CP and LMVD.